DEVELOPING CRAFT AS A CREATIVE INDUSTRY THROUGH TOURISM - Richards, Greg (2021)
This paper examines the position of crafts within the creative industries and considers how this has been affected by the growing links between the creative industries and tourism. A review of the creative industries concept indicates that crafts occupy an ambiguous position between art and tradition, which problematises their relationship with the creative industries. This is gradually changing at the creative and tourism sectors become more closely linked, and craft has become an important element of the development of creative tourism experiences. We review the role of craft in creative tourism, including case studies from Brazil, Finland, and Thailand, to examine how tourism can support the creative development of crafts. This analysis indicates that craft can be an important aspect of creative tourism development in different contexts and can provide a strong basis for placemaking initiatives.